2012
DOI: 10.1111/j.1742-481x.2012.01035.x
|View full text |Cite
|
Sign up to set email alerts
|

The possibility of microbial cellulose for dressing and scaffold materials

Abstract: In recent years, natural polymers such as cellulose, alginate and chitosan have been used worldwide as biomedical materials and devices, as they offer more advantages over synthetic polymers. The aim of this study was to clarify the usefulness of microbial cellulose (MC) for use as a dressing and scaffold material. For evaluating the biodegradability and toxicity of MC, we divided the rats (n = 12) into two groups (the implanted group and the non-implanted group). In the implanted group, we implanted the film … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(22 citation statements)
references
References 13 publications
0
21
0
1
Order By: Relevance
“…The BC used in this study was indicated as a biocompatible material without toxicity, which effectively biodegrades in vitro and is a safe-to-use material of high clinical application. Obtained BC accelerates contraction through the accumulation of extracellular matrix [104]. Moreover, Park et al in their studies indicated that bacterial cellulose wound dressings may be applied to various type of wounds such as cavity, laceration, abrasion, etc.…”
Section: Bacterial Cellulose Dressings Available In the Marketmentioning
confidence: 98%
“…The BC used in this study was indicated as a biocompatible material without toxicity, which effectively biodegrades in vitro and is a safe-to-use material of high clinical application. Obtained BC accelerates contraction through the accumulation of extracellular matrix [104]. Moreover, Park et al in their studies indicated that bacterial cellulose wound dressings may be applied to various type of wounds such as cavity, laceration, abrasion, etc.…”
Section: Bacterial Cellulose Dressings Available In the Marketmentioning
confidence: 98%
“…BC skin tissue repair biomaterials fabricated by a multilayer fermentation method display a low cytotoxicity and sustain the proliferation of human adipose derived stem cells [23]. Previous studies proved that the presence of BC can promote wound healing by accelerating contractions through the accumulation of extracellular matrix [24]. BC-based biomaterials have been reported to be applied in clinical practice to treat nonhealing foot ulcers [25].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, the group treated with HCM-SCT exhibited an 18.8% decrease in VEGF expression when compared with the GZ-treated group at 11 days post-surgery (11). Moreover, a decrease in the expression of VEGF was observed in the group treated with microbial cellulose on day 14 after skin excision, although it was higher in the same group on day 7 (38). In the present study, the number of blood vessels and the expression level of VEGF were higher in the FSCT-CM-treated group than the other groups on day 7, while their levels were lower on day 14.…”
Section: Discussionmentioning
confidence: 89%